Unusual Presentation of Recurrent Early Stage Endometrial Carcinoma 28 Years after Primary Surgery. (9th December 2015) - Franchello, Alessandro; Fronda, Gianruggero; Deiro, Giacomo; Fiore, Alessia; Cassine, Davide; Molinaro, Luca; Chiusa, Luigi; Galati, Sara; Resegotti, Andrea; Silvestri, Stefano
Abstract : Endometrial carcinoma is the most common neoplasia of female genital tract. The prognosis of early stage disease (FIGO I and FIGO II) is excellent: recurrence after surgery is less than 15%, most of which are reported within 3 years after primary treatment. Herein we report a case of late rectal recurrence from FIGO Ib endometrial adenocarcinoma. Patient had also familiar and personal history of colonic adenocarcinoma and previous findings of microsatellite instability (MSI); molecular analysis evidenced heterozygotic somatic mutation in MLH1 gene. Twenty-eight years after hysterectomy and bilateral salpingoovariectomy, a rectal wall mass was detected during routine colonoscopy. Patients underwent CT scan, pelvic MRI, and rectal EUS with FNA: histopathological and immunohistochemical analysis revealed differentiated carcinoma cells of endometrial origin. No neoadjuvant treatment was planned and low rectal anterior resection with protective colostomy was performed; histology confirmed rectal lesion as metastasis from endometrial carcinoma. Recurrence of early stage endometrial carcinoma after a long period from primary surgery is possible. It is important to keep in mind this possibility in order to set a correct diagnostic and therapeutic algorithm, including preoperative immunohistochemical staining, and to plan a prolonged follow-up program.